Krajowe bezzwrotne źródła finansowania instytucji kultury – za mało i jednocześnie zbyt wiele? - Kołaczkowski, Bartosz; Ratajczak, Małgorzata (Studia Prawa Publicznego, 2021)
Culture is one of the spheres in which human freedom is realized, and, at the same time, it is one of the main areas of public activity. The Constitution of the Republic of Poland recognizes (in Article 6) culture as the source of the identity of the Polish nation, its duration and development. In Poland, public cultural institutions definitely dominate among the entities operating in the field of culture. These are state and local government organizational units whose primary goal is to conduct cultural activity understood as the creation, dissemination and protection of culture. Cultural activity understood in this way, in accordance with the provisions adopted in Polish law, is not a commercial activity. This study deals with the issue of financing cultural institutions from non-returnable domestic funds. This subject has gained particular importance due to the deepening financial difficulties of cultural institutions as a result of the COVID-19 pandemic underway since 2020. An important argument that justifies considering the above-mentioned topic is the lack of sufficient knowledge of practitioners about the methods (sources) of financing cultural institutions. An analysis of the legal regulations regarding the own revenues of cultural institutions, subsidies, sponsorship and finally, aid instruments related to COVID-19 was performed in individual parts of the study. In order to obtain a credible picture of the financial condition of the Polish culture sector, the amount of public funds allocated in our country for its development and protection in 2011–2021 was also examined. The analysis here shows that a characteristic feature of the financing system for Poland’s culture is a large diversification of the possibilities for cultural institutions to obtain non-returnable domestic funds, which can be considered both an advantage and a disadvantage of this system.